Purple Sweet Potato Extract and Aerobic Exercise Reduce Lipid Profiles in Hyperlipidemic Rats Model - Setiyo Hartoto; Agus Hariyanto; Sholikhah Anindya Mar’atus; Shidqi Hamdi Pratama Putera; Donny Ardy Kusuma; Awang Firmansyah; Muhammad Dzul Fikri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Obesity and dyslipidemia are the major risk factors for cardiovascular disease. It has been shown that dietary supplementation combined with exercise at appropriate intensity improves lipid profile and reduces the risk of cardiovascular disease. This study investigates the effect of purple sweet potato extract and swimming training on the lipid profile of a hyperlipidemic rat model. Twenty-five male Wistar rats were grouped into standard diet and high-fat diet and given their respective diet for two weeks. Afterward, they were randomly divided into five weight-matched groups; normal control (C; n=5), high-fat diet (HF; n=5), exercise (E; n=5), purple sweet potato extract (PSP; n=5), and exercise combined with purple sweet potato extract (EPSP; n=5). Purple sweet potato extract was given 100 mg/day through oral gavage for three weeks. Swimming exercise was performed for 30 minutes/day, five days a week, for three weeks at an intensity of 6% of body weight. At the end of the experimental period, intracardiac blood samples were drawn to measure lipid profiles. Data analysis technique using a one-way ANOVA test with a significant level of 5%. The findings revealed that the concentration of TC and LDL was highest in HF. The combination of exercise and purple sweet potato extract significantly reduced LDL and increased HDL levels compared to exercise or PSP alone (p ≤ 0.05). It indicates that purple sweet potato extract combined with swimming exercise is shown to be effective in improving lipid profiles in hyperlipidemic rat models.